2013
DOI: 10.1164/rccm.201210-1843ci
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Bronchitis and Chronic Obstructive Pulmonary Disease

Abstract: Chronic bronchitis (CB) is a common but variable phenomenon in chronic obstructive pulmonary disease (COPD). It has numerous clinical consequences, including an accelerated decline in lung function, greater risk of the development of airflow obstruction in smokers, a predisposition to lower respiratory tract infection, higher exacerbation frequency, and worse overall mortality. CB is caused by overproduction and hypersecretion of mucus by goblet cells, which leads to worsening airflow obstruction by luminal ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
276
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(308 citation statements)
references
References 114 publications
(124 reference statements)
5
276
1
10
Order By: Relevance
“…Additionally, although we did not find statistical relationship between recovery period and FEV1 %pred, we found that recovery period was prolonged as severity of airflow limitation increased. Third, Mucous metaplasia and mucus overproduction are the pathologic foundation of CB (23). Therefore, we speculated that exacerbation type in patients with CB were more likely to belong to Anthonisen I/II, which was significantly associated with late recovery (17).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, although we did not find statistical relationship between recovery period and FEV1 %pred, we found that recovery period was prolonged as severity of airflow limitation increased. Third, Mucous metaplasia and mucus overproduction are the pathologic foundation of CB (23). Therefore, we speculated that exacerbation type in patients with CB were more likely to belong to Anthonisen I/II, which was significantly associated with late recovery (17).…”
Section: Discussionmentioning
confidence: 97%
“…COPD is being recognised as an increasingly diverse disease, and individuals may benefit from more tailored treatment approaches applied to NIV. Examples of tailored treatment in COPD include roflumilast for patients with chronic bronchitis 125 and lung volume reduction surgery for patients with both predominantly upper-lobe emphysema and low baseline exercise capacity. 126 Effect of different pressure settings on effectiveness of non-invasive ventilation Non-invasive ventilation pressure settings may influence effectiveness, and this report identified three RCTs directly comparing different settings.…”
Section: Effect Of Patient Characteristics On Effectiveness Of Non-inmentioning
confidence: 99%
“…Chronic bronchitis affects up to 22% of nonsmokers and 14-74% of patients with chronic obstructive pulmonary disease (COPD) (2). Chronic bronchitis has been associated with worse outcomes in COPD, including a greater exacerbation frequency, more respiratory hospitalizations, worse health-related quality of life, greater lung function decline, and possibly increased mortality (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%